PENGARUH KOMUNIKASI INTERPERSONAL GURU DAN PEMAHAMAN SISWA TERHADAP KEAKTIFAN BELAJAR SISWA DI SMKN 1 PANGKATAN - Lidya Situmorang (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2022)
This research is a quantitative study that aims to see the extent of the influence of teacher interpersonal communication and student understanding on student learning activities at SMKN 1 Pangkatan. The data of this research were obtained through observation, and the results of the questionnaires were distributed to the respondents. The sample in this study amounted to 123 students. Samples were taken using the total sample. From the results of the descriptive test, it is known that 123 respondents, there are 66 respondents (54%) stating that the interpersonal communication that is currently taking place is in a very good trend. The results of the descriptive test on student understanding showed that 123 respondents there were 47 respondents (38%) stating that the current understanding of students was in a good trend, so it could be concluded that student understanding had a significant effect on student learning activity. The contribution of interpersonal communication and student understanding simultaneously to student learning activities in SMK Negeri 1 Pangkatan is 0.793 units or 79.3%. And the remaining 20.7% is influenced by other variables not examined.Keys : Interpersonal Communication, Student Understanding, and Student Learning Activities